WISATA ZIARAH PERMUKIMAN DESA GUNUNG PRING MUNTILAN (âWayfindingâ as a solution for the Direction Sign in the Pilgrimage Village Tourism Zone in the Gunung Pring Muntilan) - Prastomo, Agustinus Dicky (Unika Soegijapranata Semarang, 2015)
Rural areas generally offer a natural beautiful green atmosphere both social, economic, cultural, religious, traditions, architecture of the building as well as the arrangement of the different neighborhoods of the city. The existence of a religious pilgrimage site based in the village of Gunung Pring Muntilan, Central Java raises the potential for rural development. But the arrival of pilgrims in the village of Gunung Pring especially in the summer season approaching month of Ramadan or other pilgrimages often affect the circulation path that led to the problems of congestion. Although the environment has been reorganized, still appears the issue of seasonal population density and traffic congestion. Structuring the housing environment (zoning) that has been done has not been followed by the provision of design information such as the identity of the name and directions for pedestrians and vehicles passing around the tourist zone of pilgrimage village of Gunung Pring. This paper aims to identify and describe the design needs wayfinding information such as driving directions in the solution (zone) pilgrimage Mount Pring. The study was conducted by using descriptiveanalytical analysis. The findings of the study revealed, it takes adequate directions so that the circulation path to be smooth